2021
DOI: 10.1128/spectrum.01645-21
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Benefit Plants Performance by Augmenting Arbuscular Mycorrhizal Symbiosis

Abstract: Brassinosteroids (BR) and Arbuscular mycorrhizas (AM) symbiosis play an important role in improving plant growth and development. Previous studies have shown that there is a complex regulatory network between phytohormones and AM symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…One of the major end products of the BR biosynthetic pathway is 24-epibrassinolide (24-epiBL), which has been shown to activate pathogenesis-related genes and protect plants from biotic stress damage, e.g., by Fusarium [ 62 , 64 ]. In addition, a study on Eucalyptus grandis showed that treatment with 24-epiBL had a significant positive effect on mycorrhizal colonization and the abundance of arbuscular mycorrhiza (AM) fungi in E. grandis roots [ 65 ]. Whereas 24-epiBL down-regulates BRH1 expression [ 66 ], treatment with 24-epiBL induces OFP8 expression and results in increased OFP8 protein accumulation, as shown in a study in rice [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major end products of the BR biosynthetic pathway is 24-epibrassinolide (24-epiBL), which has been shown to activate pathogenesis-related genes and protect plants from biotic stress damage, e.g., by Fusarium [ 62 , 64 ]. In addition, a study on Eucalyptus grandis showed that treatment with 24-epiBL had a significant positive effect on mycorrhizal colonization and the abundance of arbuscular mycorrhiza (AM) fungi in E. grandis roots [ 65 ]. Whereas 24-epiBL down-regulates BRH1 expression [ 66 ], treatment with 24-epiBL induces OFP8 expression and results in increased OFP8 protein accumulation, as shown in a study in rice [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the propagation of R. irregularis in Z. mays roots, 100 mL of Hoagland’s solution at 1% of the standard Pi concentration (1 mM) were applied directly every 15 days into pots to satisfy the growth requirements of Z. mays and maintain an appropriate low phosphorus condition for R. irregularis . After propagation, the inoculum obtained through sucrose gradient centrifugation was used as the spore agent ( Ren et al, 2021 ). 14-day-old seedlings of perennial ryegrass were inoculated with around 400 spores by applying 1 mL of an aqueous solution near the root system.…”
Section: Methodsmentioning
confidence: 99%
“…Et Zucc ( Sun et al., 2022 ). However, the effect of different AMF species on the accumulation of plant metabolites varies greatly ( Majewska et al., 2017 ; Ren et al., 2021 ; Ran et al., 2021a ; Marro et al., 2022 ). Therefore, choose suitable AMF agents is a key step to improve the accumulation of active substances within plants.…”
Section: Introductionmentioning
confidence: 99%